Elimination of Intravenously Administered Radiolabelled Antithrombin III and Heparin in Humans - de Swart, Cees A M; Nijmeyer, Bertha; Andersson, Lars-Olov; Holmer, Erik; Sixma, Jan J; Bouma, Bonno N (Thrombosis and Haemostasis, 1984)
Antithrombin III was purified from normal plasma by DEAE- Sephadex chromatography and heparin affinity chromatography; the protein was subsequently radiolabelled with 125I. 125I-anti- thrombin III alone and 125I-antithrombin III in the presence of high affinity 35S-heparin fractions were injected into normal humans. 125I-radiolabel and protein bound 35S-radioactivity were followed separately. In semilogarithmic plots 125I-antithrombin III disappeared according to a double exponential curve with a half-life in the second phase of 56.8 hr in the absence of heparin and of 33.7 hr in the presence of heparin. Protein bound 35S- radioactivity disappeared much faster than the 125I-radiolabel. These data support the concept that heparin disappears as free heparin from the equilibrium heparin – antithrombin III ⇄ heparin + antithrombin III. Immuno-reactive antithrombin III decreased from 100% to 85-90% immediately after injection of 125I-antithrombin III in the presence of heparin and returned to normal values within 30 min. This suggests that antithrombin III is transiently sequestered, possibly in trimolecular complexes consisting of antithrombin III, heparin and either lipases or other vascular bound proteins.
Keywords: Heparin; Antithrombin III; Turnover of heparin and antithrombin III